Histopathologic features of esophageal glands in the region of the gastroesophageal junction in Chinese patients with gastric cardiac cancer involving the esophagus - Qin Huang; Lihua Zhang (Dove Medical Press, 2010)
Qin Huang1,2,3, Lihua Zhang11Department of Pathology of the Nanjing Drum Tower Hospital, Nanjing, China; 2Department of Pathology and Laboratory Medicine, Veterans Affairs, Boston Healthcare System, West Roxbury, MA, USA; 3Harvard Medical School, Boston, MA, USAAbstract: Esophageal glands (EGs) were implicated previously as a potential origin of carcinomas of the gastroesophageal junction (GEJ). The studies of histopathology on diseases in EGs, however, are scarce. In the present study, we systematically investigated EGs in 36 resection cases of gastric cardiac carcinomas involving the esophagus (GCE) in Chinese patients. All cases showed chronic inflammation in EGs and 14 (39%) with Helicobacter pylori infection. Hyperplasia, atrophy, and dysplasia were common in EGs and observed in 21 (58%), 14 (39%), and 28 (78%) cases, respectively. These changes were associated with various types of metaplasia, including intestinal (6, 17%), oncocytic (26, 72%), pancreatic acinar (11, 30%), and squamoid metaplasia (8, 22%). Oncocytic metaplasia was patchy, frequently replaced the entire lobule with dysplastic features. Pancreatic acinar metaplasia was present in superficial EGs as small acinar patches. Squamoid metaplasia was limited to the EG drainage ductile epithelium without keratin pearls or intercellular bridges; however, cytoplasmic vesicles and secretory vacuoles were common, suggesting dual differentiation. Dysplastic EGs featured architectural disarray with fused acini, cribriforming, abortive growth, and nuclear hyperchromasia, enlargement, and overlapping. The results demonstrate a spectrum of histopathologic changes in EGs and ductile epithelium, which is similar to those observed in GCE in Chinese patients.Keywords: esophageal glands, esophagus, stomach, cancer, Chinese